The Effect of Using Wordwall Website as a Strategy on Students' Vocabulary Mastery - Darmawati Darmawati; Nayla Nayla (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study investigated the effectiveness of using the Wordwall website as a learning strategy to enhance students' vocabulary mastery. Employing a quasi-experimental design, the research involved a control group and an experimental group from [mention specific school/level, e.g., a junior high school in Medan]. Data were collected using a vocabulary test (pre-test and post-test) and analyzed using t-test statistical analysis. The findings indicated a significant improvement in vocabulary mastery among students in the experimental group who utilized the Wordwall website compared to the control group. This suggests that the Wordwall website is an effective and engaging tool for improving students' vocabulary acquisition. The study recommends the integration of interactive digital platforms like Wordwall into language learning curricula to support vocabulary development.